From gut to liver: unveiling the differences of intestinal microbiota in NAFL and NASH patients - Huang, Furong; Lyu, Bo; Xie, Fanci; Li, Fang; Xing, Yufeng; Han, Zhiyi; Lai, Jianping; Ma, Jinmin; Zou, Yuanqiang; Zeng, Hua; Xu, Zhe; Gao, Pan; et al. (Frontiers in Microbiology, 2024)
Gut microbiota play a pivotal role in the pathogenesis of Non-alcoholic fatty liver disease (NAFLD). However, there remains limited understanding regarding the characteristics and ecological alterations of gut microbial communities during the progression of Non-alcoholic fatty liver (NAFL) to Non-alcoholic steatohepatitis (NASH). To address this point, we comparatively analyzed the gut microbiota composition of NAFL and NASH to obtain the characteristics and differences of their intestinal gut microbiota. The healthy group (65 cases), NAFL group (64 cases), and NASH group (53 cases) were compared using 16S rRNA sequencing, random forest machine learning, and database validation. It was observed that the diversity of intestinal flora gradually decreased during the progression of NAFLD disease (p < 0.05). At the phylum level, both NAFL and NASH patients exhibited high abundances of Bacteroidetes and Fusobacteria, while Firmicutes had low abundances. At the genus level, there was a significant decrease in the expression of Prevotella in the NAFL group (AUC 0.738). Conversely, the AUC value for Megamonas and Fusobacterium combination in the NASH group was 0.769. KEGG pathway analysis revealed significant disturbances in multiple types of glucose metabolism in the NASH group compared to NAFL group, as well as a significantly inadequate function in flavonoid and flavonol biosynthesis. In conclusion, this study reveals specific microbiota characteristics and intestinal microecological changes in the progression of NAFL to NASH, paving the way for the study of new biomarkers and therapeutic targets for NAFLD.